A mouse model of post-stroke pneumonia induced by intra-tracheal inoculation with Streptococcus pneumoniae - Mracskó, Eva; Stegemann-Koniszewski, Sabine; Na, Shin-Young; Dalpke, Alexander; Bruder, Dunja; Lasitschka, Felix; Veltkamp, Roland (Cerebrovascular diseases, 2017)
Background: Stroke-induced immunodeficiency increases the risk of infectious complications, which adversely affects neurological outcome. Among those, pneumonia affects as many as one third of stroke patients and is the main contributor to mortality in the post-acute phase of stroke. Experimental findings on post-stroke susceptibility to spontaneous pneumonia in mice are contradictory. Here, we established a mouse model inducing standardized bacterial pneumonia and characterized the impaired pulmonary cellular and humoral immune responses after experimental stroke. Methods: Bacterial pneumonia was induced by intra-tracheal inoculation with Streptococcus pneumoniae at different time points after transient middle cerebral artery occlusion (MCAO). Bacterial counts in lungs and blood, histological changes, and cytokine production in the lungs were assessed. Furthermore, we investigated the effect of pneumonia on stroke outcome. Results: Intra-tracheal inoculation resulted in reproducible pneumonia and bacteraemia, and demonstrated post-stroke susceptibility to streptococcal pneumonia developing with a delay of at least 24 h after MCAO. Higher bacterial counts in mice infected 3 days after stroke induction correlated with reduced neutrophil and macrophage infiltration in the lungs and lower levels of pro-inflammatory cytokines in the broncho-alveolar lavage compared to sham-operated animals. Pneumonia increased mortality without affecting brain-infiltrating leukocytes. Conclusions: In this standardized mouse model of post-stroke pneumonia, we describe attenuated leukocyte infiltration and cytokine production in response to bacterial infection in the lungs that has a profound effect on outcome.